Development of Levan capped silver nanoparticles based product and its effect on wound healing - Jasmin Kubavat; Jayrajsinh Sarvaiya; Tushar Tyagi; Sugato Banerjee; Punita Aggarwal (Elsevier, 2023)
Silver nanoparticles (AgNPs) are extensively investigated for their potential physical, chemical, and biological properties. Silver nanoparticles (AgNPs) have several applications in diagnosis, therapy (wound healing, cancer), electronic devices, water treatment, etc. The present study used the cost-effective and ecologically approachable technique to synthesize levan-capped silver nanoparticles of about 22 nm. These silver nanoparticles were subsequently introduced into a gel to create a silver release system with bacteria inhibition activity. The study also aimed to evaluate synthesized Levan-based silver nanoparticles loaded gel for its wound healing property in the excision rat model. Compared to commercial products, levan-based AgNPs were used for in-vitro antimicrobial activities on E. Coli and Staphylococcus aureus and in-vivo wound healing properties.The wound healing property was assessed by area and time of wound closure in rats. In the excision wound model, Levan-based AgNPs exhibited a reduction in wound area that was more as compared to standard and control. In this study, the nanoparticles of silver were spherical and homogeneous in size, which showed bactericidal effects for E. coli and B. subtilis. Levan acts as a coating and reducing agent for silver nanoparticles and acts as an anti-inflammatory agent in the healing process. Carbopol was used for topical formulations such as hydrogel due to high viscosity at low concentration and low toxicity profile. This polymer is anionic that needs to be neutralized with triethanolamine to become jellified, and it has good bio-adhesive properties required for gel formulation. The present challenge of silver nanoparticles (AgNPs) is to maximize their benefits and minimize their toxic effects on humans and the environment. For future perspective, its synthesis, release into the atmosphere, and scaling up production must be considered.